COMPETITIVENESS OF THE REGION AS A TRANSFORMATION BASIS FOR THE ECONOMY OF THE REPUBLIC OF KAZAKHSTAN - Arynova, Zh.Z.; Abdykarimova A.Т.; Zhetpisbayeva M.К.; Salzhanova, Z.A.; Kuttybaeva, N.B.; Kenges, G.K. (Scientific Journal of Pedagogy and Economics, 2020)
In the era of globalization, the development of countries with a small open economy largely depends on the intensity of using various forms of international economic relations, among which the competitiveness of each country plays a special role. At the present stage of development, the problem of competitiveness is central to the economic policy of the state. Creating competitive advantages over an opponent becomes a strategic direction of the state and its bodies and applies to all levels of the hierarchy: products (goods and services), enterprises, industries, regions and the country as a whole, but the country’s competitiveness is of particular importance. The competiti-veness of the region is determined in comparison with other similar facilities. This characteristic refers to estimated indicators, therefore, it assumes, along with the subject and subject of the assessment, the presence of certain criteria. Evaluation criteria (goals) may be the market position, the pace of development, the ability to pay for the borrowed funds received, consumer properties in relation to the price of the goods, etc.